Work-Life Balance Among Generation Z Employees At Bank Bri Semarang Regional Office - Farah Atiqah (Publikasi Indonesia, 2025)
The rising involvement of Generation Z in the banking sector introduces new challenges regarding work-life balance (WLB). This generation places strong emphasis on flexibility, mental well-being, and a healthy balance between personal life and work, while the banking industry is characterized by high pressure, long working hours, and hierarchical structures. This study aims to explore how Generation Z employees at Bank BRI Regional Office Semarang perceive work-life balance, the obstacles they encounter, and the strategies they employ to maintain balance. Using a qualitative phenomenological approach, in-depth interviews were conducted with five Generation Z employees and two managerial informants for triangulation. The findings reveal that Gen Z interprets WLB not only as time allocation, but also psychological involvement, emotional satisfaction, and the ability to manage boundaries between work and personal life, aligned with the principles of Border Theory. Key barriers identified include extended working hours, significant overtime demands, mechanistic organizational culture, and limited schedule flexibility. Despite these challenges, Gen Z employees adopt several strategies such as effective time management, priority setting, assertive communication, and reliance on social support and digital tools for self-recovery. The study provides theoretical contributions by extending the application of Border Theory to the context of Gen Z in Indonesia’s banking industry and practical contributions by offering recommendations for designing adaptive work policies that enhance the well-being and retention of young employees.